A systematic decision-making approach to optimizing microgrid energy sources in rural areas through diesel generator operation and techno-economic analysis: A case study of Baron Technopark in Indonesia - Prawitasari, Adinda; Nurliyanti, Vetri; Putri Utami, Dannya Maharani; Nurdiana, Eka; Akhmad, Kholid; Aji, Prasetyo; Syafei, Suhraeni; Ifanda, Ifanda; Mulyana, Iwa Garniwa (International Journal of Renewable Energy Development, 2024)
Microgrid systems are part of the most reliable energy supply technologies for rural communities that do not have access to electricity but the system is generally dominated by diesel generators (DG). The implementation of de-dieselization programs to ensure efficient diesel operations requires addressing several scenarios such as the replacement of diesel completely with 100% renewable energy sources at a significant cost. The design and selection of appropriate configuration, as well as operating patterns, need to be considered in adopting economical and reliable microgrid systems. Therefore, this study aimed to design an optimal configuration and operational pattern for microgrid systems for the frontier, outermost, and least developed (3T) regions using Baron Techno Park (BTP) in Indonesia as a case study. The optimization was conducted through HOMER software combined with benefit-cost analysis and the focus was on daily load variations, selection of control algorithms, reconfiguration of the power supply system, and setting of the diesel generator operating hours. The results showed that the optimum configuration was achieved using loads of resort, 24 kWp of PV, 288 kWh of BESS, load-following (LF) as dispatch controller, and 25 kVa of DG. Moreover, the proposed microgrid system produced 12% excess energy, 36% renewable fraction (RF), 13.25 tons reduction in CO2 emissions per year, $0.28 LCOE per kWh, $250,478 NPC, and a benefit-cost ratio (BCR) of 0.89. It also had a potential energy efficiency savings of 55.56% and a cost efficiency of 20.95% compared to existing system configurations. In conclusion, the study showed that the addition of DG to microgrid systems in 3T areas was more optimal than using only PV and batteries. An effective operating schedule for the DG was also necessary to improve RF and reduce expenses. Furthermore, other energy storage devices considered less expensive than batteries could be introduced to improve the economics of microgrid systems in the 3T region.